1973
DOI: 10.1159/000240623
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Studies on the Human Growth Cartilage in Fetuses and Newborns

Abstract: Microchemical determination of hexosamine and hydroxyproline performed in isolated histological zones from sections of tibial epiphyseal plate obtained from fetuses, newborn infants and children showed a decrease of hexosamine and an increase of hydroxyproline concentration with age. Fractionation of glycosaminoglycans demonstrates that the differences in hexosamine are due mainly to variations in chondroitin sulphates. Gel electrophoresis of protoeglycans showed different patterns in fetuses and in older chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

1975
1975
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…A similar change was found in humans (16). It was the purpose of this study to determine when the pattern of the fetal proteo glycans of human growth cartilage is converted into the pattern found in older children.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…A similar change was found in humans (16). It was the purpose of this study to determine when the pattern of the fetal proteo glycans of human growth cartilage is converted into the pattern found in older children.…”
supporting
confidence: 57%
“…In a previous study (16) we found that in various species (rat, pig, baboon) the gel-electrophoretic pattern of fetal growth cartilage proteoglycans is different from that found in older animals.…”
Section: Discussionmentioning
confidence: 78%
“…Мономер протеогликана хряща [4,23] [34]. В эмбриональ ном хряще ГАГ представлены главным образом ХС-4 и ХС-6, а также гепарансульфатом [11,13,39,50]. В процессе эмбрионального развития ко личество гепарансульфата в хрящевой ткани падает, а кератансульфата нарастает.…”
unclassified